FAKTOR -FAKTOR PENGHAMBAT PENGELOLAAN ANGGARAN BELANJA MODAL PADA KANTOR PELAYANAN PERBENDAHARAAN NEGARA MAKASSAR II - Nashriah Akil (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
Objective to determine the factors - factors inhibiting the budget management at the State Treasury Office Makassar II, Peneliitan is implemented in the city of Makassar. Methods Data used in this research is secondary data, ie data on the Central Government Financial Statements (LKPP), Government Financial Statements in Makassar State Treasury Office II.Teknik data collection in this study is documentation, which collects data based on documents - documents and reports tertulis..Metode data analysis is descriptive quantitative measurement of effectiveness. Results showed capex by the scope of the work unit Makassar II daritahun KPPN payments from 2013 to 2015 can be said to be very effective and the only factor that inhibits the administrative budget management